Metaheuristic methods for optimizing the quality of service of composite web services - Moroz, H.B. (PROBLEMS IN PROGRAMMING, 2025)
With the advent of service-oriented architectures, it has become possible to register, invoke, and aggregate web services based on their identical quality of service attributes to create composite web services with added value that meet user needs. However, the rapid introduction of new web services into a dynamic business environment can negatively affect their quality of service. Therefore, the question of how to capture, aggregate, and use information about the quality of service of individual web services to obtain an optimal end-to-end quality of service of a composite web service is currently one of the priority research areas in software engineering and service-oriented computing. This paper presents the basic theoretical information necessary to understand the importance, multifacetedness, and complexity of the problem of web service composition taking into account their quality of service, as well as a representative overview of the use of methods global optimization metaheuristic, which have been the dominant methods for solving this problem over the past two decades. The purpose of the work is to draw the attention of students and the scientific community to the current problems of web service composition that arise in the Internet of Things, cloud computing, social networks, mobile computer and smartphone technologies, etc., and to involve them in active participation in solving these problems.Problems in programming 2025; 3: 3-18